Pendampingan Pijat Oketani Dalam Meningkatan Produksi ASI Pada Ibu Nifas Di Kabupaten Bulukumba - Husnul Khatima; Kurniati Akhfar (JCS, 2025)
Exclusive breastfeeding has great benefits for babies and mothers. However, some postpartum mothers experience problems in the breastfeeding process, such as poor breast milk production and ineffective latching. One method that can help overcome this problem is oketani massage. Oketani massage is a lactation massage technique that can help increase breast milk production by stimulating the mammary glands and improving blood flow in the breast area. In this case, community service activities aim to accompany postpartum mothers in applying the oketani massage technique to increase breastfeeding success by involving the husband's role as the main supporter as an alternative solution to breastfeeding problems in the community. This service was carried out in Paenre Lompoe Village, Gantarang District, Bulukumba Regency with 5 postpartum mothers and their husbands participating. The methods used include counseling, demonstrations and direct practical assistance. The results of the activity showed an increase in participants' understanding of the benefits of oketani massage and their ability to apply the technique independently. With this assistance, it is hoped that postpartum mothers and husbands will be more confident in providing support for the success of exclusive breastfeeding and overcoming the lactation problems they face.